Long-term consumption of plant stanol and sterol esters, vascular function and genetic regulation - Gylling, Helena; Hallikainen, Maarit; Raitakari, Olli T; Laakso, Markku; Vartiainen, Erkki; Salo, Pia; Korpelainen, Vesa; Sundvall, Jouko; Miettinen, Tatu A (British journal of nutrition, 2009)
Polymorphisms of the ABCG5 and ABCG8 genes interfere with cholesterol absorption and synthesis. We determined whether common polymorphisms of these genes regulate the responses of serum cholesterol and vascular function during long-term inhibition of cholesterol absorption. Mildly to moderately hypercholesterolaemic subjects (n 282) completed a 1-year study consuming plant stanol or sterol ester (2 g stanol or sterol) or control spread. Serum cholesterol and non-cholesterol sterols, markers of cholesterol absorption and synthesis, and variables of vascular function and structure were analysed in relation to common polymorphisms of ABCG5 and ABCG8. At baseline, subjects with the 54K allele of ABCG8 had higher brachial endothelial-dependent flow-mediated dilatation than those without it (5·79 (se 0·31) v. 4·46 (se 0·44) %; P = 0·049), and subjects with the 632V allele of ABCG8 had larger brachial artery diameter than those without it. Polymorphisms of ABCG5 and ABCG8 were neither associated with serum cholesterol reduction nor changes in cholesterol metabolism or in vascular function. However, in subjects with the 400K allele of ABCG8, intima media thickness (IMT) was increased in all groups more than in those without it (P < 0·05). In conclusion, serum cholesterol lowering with absorption inhibition was not associated with polymorphic sites of ABCG5 and ABCG8. However, regulation of baseline cholesterol metabolism and vascular function and structure, and IMT progression during 1 year seemed to share some of the common polymorphic sites of these genes, suggesting a gene-regulated interaction between cholesterol metabolism and vascular function and structure.